ANALISIS PENGARUH HAMBATAN SAMPING AKIBAT AKTIVITAS PASAR PITALAH KABUPATEN TANAH DATAR - Mulia, Putra; Dewi, Selpa; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The increase in the number of vehicles owned by the community today is not in line with the growth of transportation infrastructure. This has resulted in various problems, especially traffic jams that are difficult for the government to overcome. In the Regency area, especially in Pasar Pitalah located in Nagari Pitalah, Batipuh District, Tanah Datar Regency, it is a connecting road between districts / cities. Market activity in the area causes side barriers that affect traffic flow. The purpose of this study was to determine the level of side resistance and analyze its effect on the performance of the Padang Panjang-Solok road. The study was conducted through a side obstacle survey to see traffic disturbances and a traffic volume survey to see the density of vehicles passing through the area. The calculation is based on the Indonesian Road Capacity Guidelines PKJI'14 for roads outside the city. The results showed that the weight of side obstacles that occurred was 878 events, with the highest degree of saturation reaching 0.46 and the total vehicle volume of 1075 skr / hour. The capacity of the road section is 2461,7 skr / hour. Therefore, it can be concluded that the Pasar Pitalah road section belongs to a very high class of side obstacles. Therefore, it is recommended to install traffic signs and put pedestrians in order during peak days of market activity.Keywords : Side obstacles, congestion, traffic volume, PKJI'14